The reproductive potential of uterus transplantation: future prospects - Gullo, Giuseppe; Etrusco, Andrea; Fabio, Manuela; Cucinella, Gaspare; Rossi, Claudio; Billone, Valentina (Acta Biomedica Atenei Parmensis, 2022)
Background and aim:Absolute uterine factor infertility (AUFI) is a form of infertility whereby conception and/or maintenance of pregnancy is impossible as a result of uterine absence or its completed dysfunction. It affects 1/500 women of reproductive age while the incidence is about 8% of infertile couples. Uterus transplantation (UTx) has been gaining ground as a viable option to enable women with AUFI to have biological children and as an alternative to surrogacy, a highly controversial practice still banned in many countries. Methods:The authors have set out to strike a reasonable balance between UTx benefits and the still numerous risks, whether clinical or ethical, associated with such an innovative form of transplant, which is not life-saving, requires immunosuppression throughout pregnancy and the organ to be removed right after childbirth. Results: While still far from achieving mainstream status, considerable strides have been made in UTx outcomes, with many live births already recorded. Procedures from living donor are reportedly more effective in terms of success rates. Organ tissue engineering has been explored and developed with promising results. Conclusions: UTx entails various risks and ethical quandaries which have to do with reproductive autonomy and rights. New human attempts and clinical trials of UTx should be performed to further optimize the procedure in relation to safety and effectiveness. Techniques such as tissue engineering could lead in the medium-long term to a wholly bioengineered uterus to be used for transplantation, relying on scaffolds from decellularized organs or tissues that can be recellularized by several types of autologous somatic/stem cells. Such advances hold promise in terms of solving UTx-related complications and organ supply difficulties.